The role of measurement in economics - Stone, Richard, 1913-1991 (Cambridge : Cambridge University Press, 2013)
First published in 1951, and originally delivered as the Newmarch Lectures for 1948-9, this book examines the role of measurement in obtaining and applying economic knowledge. Esteemed economist Richard Stone, who went on to win the Nobel Prize in Economics, divides his topic into four sections: questions of fact and empirical constructs; the truth or falsity of a hypothesis; the estimation of parameters; and questions of prediction. This book will be of value to anyone with an interest in economics and the development of the discipline.
Title from publisher's bibliographic system (viewed on 06 Jun 2016).
Keywords: Index numbers (Economics); Economics